Implementation and use of standardized outcome measures by physical therapists in Saudi Arabia: barriers, facilitators and perceptions - Tahani N. Al-Muqiren; Einas S. Al-Eisa; Ahmad H. Alghadir; Shahnawaz Anwer (BMC, 2017)
Abstract Background The use of standardized outcome measures (SOMs) has been recommended in the physical therapy practice guidelines to improve the patient's management and encourage the evidence based practice. However, the extent of the use of SOMs by physical therapists (PTs) in Saudi Arabia was not investigated. The present study aimed to (1) evaluate the extent of the use of SOMs by PTs in routine daily practice in Saudi Arabia; (2) explore the barriers, facilitators and perceptions in the use of SOMs during physical therapy services; (3) examine the relationship between facility settings and the PTs characteristics and the use of SOMs. Methods The present study used an observational design. A survey based questionnaire used and distributed to 352 PTs who were working in Saudi Arabia and was commonly involved in the management of patients within different clinical settings, either private or public. Results One-hundred-eighty participants completed the questionnaires (response rate of 51%). One-hundred-eleven (62%) participants indicated that they used SOMs in their practice. The most common barriers to using the SOMs were time-consuming for patients and therapist and difficult to understand the outcome measures by the patients. Those with a Masters degree were 3.5 times more likely to use SOMs compared to PTs with diploma level qualification [Odd Ratio (95% CI) 3.5 (0.9-12.6)]. Participants with a clinical specialty were nearly 3 times more likely to use SOMs than those who do not have a specialty [Odd Ratio (95% CI) 2.9 (1.6-5.5)]. Conclusions Nearly two-thirds of the participants indicated that they used SOMs in clinical practice. Time-consuming for patient and therapist, difficult to understand the SOMs by the patients were the main perceived barriers. Years of experience, professional degree, and clinical specialty had a high probability of using SOMs. The majority of the participants showed the willingness to use SOMs in the future.